A phylogenetic circumscription of Silene sect. Siphonomorpha (Caryophyllaceae) in the Mediterranean Basin. Issue 1 (7th February 2017) - Naciri, Yamama; Du Pasquier, Pierre-Emmanuel; Lundberg, Magnus; Jeanmonod, Daniel; Oxelman, Bengt
Abstract: Silene sect. Siphonomorpha (Caryophyllaceae) has historically either been split into three different and homogeneous entities (sect. Italicae, sect. Paradoxae, sect. Siphonomorpha s.str.) or considered as a single group (sect. Siphonomorpha s.l.). In this study, we investigate the delimitation of sect. Siphonomorpha s.l. and the three subgroups, in order to sort out previous taxonomic concepts. We first performed an analysis of nuclear ribosomal internal transcribed spacer (ITS) sequences with wide taxonomic sampling to place sect. Siphonomorpha within the genus. Then, using nuclear and chloroplast sequences in a multi‐species coalescent context, we constructed two species trees with independent specimen sampling. One was based on ITS, the nuclear RPA2 gene, and the plastid rps16 gene, the other used ITS and the plastid trnH‐psbA and trnS‐trnG regions. The results are congruent among the three analyses and show that sect. Siphonomorpha s.l. is not supported as being monophyletic and that an extended concept of this section would include species also belonging to sections Saxifragoideae, Coronatae, Tataricae, Chloranthae, Barbeyanae, Nanosilene, Otites, Koreanae, Brachypodae, Graminiformes, Dianthoidea, Longitubulosae and Holopetalae. However, the three entities " Italicae ", " Paradoxae " and " Siphonomorpha s.str." are monophyletic with minor alterations and deserve taxonomic recognition as sections. Several ambiguous species are now resolved, among them the position of S. gigantea which is shown to be a highly supported clade, sister of sect. Italicae, that could therefore be named sect. Giganteae.